A review: aluminum nitride MEMS contour-mode resonator*Project supported by National Natural Science Foundation (Nos. 61274001, 61234007, 61504130), the Nurturing and Development Special Projects of Beijing Science and Technology Innovation Base's Financial Support (No. Z131103002813070), and the National Defense Science and Technology Innovation Fund of CAS (No. CXJJ-14-M32). (October 2016) - Hou 侯, Yunhong 云虹; Zhang 张, Meng 萌; Han 韩, Guowei 国威; Si 司, Chaowei 朝伟; Zhao 赵, Yongmei 咏梅; Ning 宁, Jin 瑾
Abstract: Over the past several decades, the technology of micro-electromechanical system (MEMS) has advanced. A clear need of miniaturization and integration of electronics components has had new solutions for the next generation of wireless communications. The aluminum nitride (AlN) MEMS contour-mode resonator (CMR) has emerged and become promising and competitive due to the advantages of the small size, high quality factor and frequency, low resistance, compatibility with integrated circuit (IC) technology, and the ability of integrating multi-frequency devices on a single chip. In this article, a comprehensive review of AlN MEMS CMR technology will be presented, including its basic working principle, main structures, fabrication processes, and methods of performance optimization. Among these, the deposition and etching process of the AlN film will be specially emphasized and recent advances in various performance optimization methods of the CMR will be given through specific examples which are mainly focused on temperature compensation and reducing anchor losses. This review will conclude with an assessment of the challenges and future trends of the CMR.